Unpacking the 'black box' of lay health worker processes in a US-based intervention. (1st December 2018) - Burke, Nancy J; Phung, Kristine; Yu, Filmer; Wong, Ching; Le, Khanh; Nguyen, Isabel; Nguyen, Long; Guan, Alice; Nguyen, Tung T; Tsoh, Janice Y
Summary: Prior studies have supported the effectiveness of the use of Lay Health Workers (LHWs) as an intervention model for managing chronic health conditions, yet few have documented the mechanisms that underlie the effectiveness of the interventions. This study provides a first look into how LHWs delivered a family-based intervention and the challenges encountered. We utilize observation data from LHW-led educational sessions delivered as part of a randomized controlled trial (RCT) designed to test a LHW outreach family-based intervention to promote smoking cessation among Vietnamese American smokers. The RCT included experimental (smoking cessation) and control (healthy living) arms. Vietnamese LHWs were trained to provide health information in Vietnamese to groups of family dyads (smoker and family member). Bilingual, bicultural research team members conducted unobtrusive observations in a subset of LHW educational sessions and described the setting, process and activities in structured fieldnotes. Two team members coded each fieldnote following a grounded theory approach. We utilized Atlas.ti qualitative software to organize coding and facilitate combined analysis. Findings offer a detailed look at the 'black box' of how LHWs work with their participants to deliver health messages. LHWs utilized multiple relational strategies, including preparing an environment that enables relationship building, using recognized teaching methods to engage learners and co-learners as well as using humor and employing culturally specific strategies such as hierarchical forms of address to create trust. Future research will assess the effectiveness of LHW techniques, thus enhancing the potential of LHW interventions to promote health among underserved populations.